The Influence Of Corporate Social Responsibility On Corporate Image With Green Product Innovation As A Mediating Variable - Dicky Dwi Irawan; Susilowati , Christin (Universitas Airlangga, 2025)
This research was carried out in order to give an analysis towards the affect of corporate social responsibility on corporate image with green product innovation as mediation on active Generation Z students at Brawijaya University who are consumers of AQUA brand bottled drinking water. The design of this reseacrh is called explanatory research while the approach used is quantitative. The variables in this study consist of corporate social responsibility, corporate image, and green product innovation. The research sample amounted to 112 respondents from the population of active generation Z students at Brawijaya University who consume AQUA brand bottled drinking water. The technique used to gain the sample of this research is called non-probability sampling with purposive sampling, while data collection is through a questionnaire. Data analysis using the Partial Least Square (PLS) method with the help of SmartPLS 4.1.0.6 software. The results of research conduct with several series of tests show that corporate image is impacted by social responsibilities. Corporate social responsibility affects green product innovation. Green product innovation affects corporate image. Green product innovation mediates corporate social responsibility on corporate image.